PENGARUH ATRIBUT PRODUK YANG DIPERTIMBANGKAN DALAM PEMILIHAN PRODUK DEPOSITO PERBANKAN TERHADAP KEPERCAYAAN DAN DAMPAKNYA PADA LOYALITAS NASABAH - Gunarto Suhardi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2008)
Trust is the critical element in banking product. Without consumer trust, banking industry will face a difficulties to create a true loyalty. Attribute product can help banking industry to create consumer trust by creating a product which has an important attribute by which consumer make a consideration whether the bank is credible or not. The aim of this research is to find out attribute that is important in consumer persepective and how would those attribute affecting their trust and their loyalties to the bank. Exploratory factor analysis was used to find the most important attribute product. The exploratory factor analysis result then analyized with structural equation modeling to calculate the effect of the important attribute to the consumer trust and loyalty. As a result, they are 2 factor which are Flexibility factor and Bank Competencies factor as an important attribute product which has affected trust and loyalty as well.Keywords : trust, banking, attribute product, loyalty, deposito